2020
DOI: 10.1016/j.foodchem.2020.126209
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oligosaccharides on particle structure, pasting and thermal properties of wheat starch granules under different freezing temperatures

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(28 citation statements)
references
References 37 publications
(35 reference statements)
0
24
1
Order By: Relevance
“…Changes in particle size after freezing, either larger or smaller, were reported by Yu et al. [ 24 ] Smaller particle size resulted from fragmentation of the starch granules due to expansion of ice crystals during freezing, while larger particle sizes resulted from physical swelling during freezing and denser starch aggregation [ 18 ] or small fragments deposited on the starch granule surface. [ 8 ] Liu et al.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Changes in particle size after freezing, either larger or smaller, were reported by Yu et al. [ 24 ] Smaller particle size resulted from fragmentation of the starch granules due to expansion of ice crystals during freezing, while larger particle sizes resulted from physical swelling during freezing and denser starch aggregation [ 18 ] or small fragments deposited on the starch granule surface. [ 8 ] Liu et al.…”
Section: Resultsmentioning
confidence: 96%
“…[ 25 ] found that dry matter of the granules leached out after the freeze‐thawing process, while Su et al. [ 18 ] stated that amylose was dissolved out of the granules. The glue‐like substance noticed in SEM was leached material from the starch granules.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After adding 100 mL of deionized water to each mixture and stirring the mixtures for 20 min, they were allowed to stand at 25 °C for 30 min to prepare starch‐KGM mixed solutions having a KGM concentration of 0%, 0.5%, 1.5%, 2.5%, 3.5%, and 4.5% (w/w). [ 57,58 ] Later, the mixtures were frozen and stored successively at −70 °C for 2 h, at −20 °C for 46 h, and at 25 °C for 6 h. After this process, the mixtures were lyophilized, ground, and passed through a 200‐mesh sieve. The final powders (the samples) were stored in the dryer for further characterization.…”
Section: Methodsmentioning
confidence: 99%
“…Oligosaccharides are soluble in water, and their sweetness is 0.3–0.6 times that of sucrose. Low sweetness makes them an ideal substitute for sucrose in foods for patients with diabetes, heart disease or thrombosis (Su et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%